53% Efficient Red Emissive Carbon Quantum Dots for High Color Rendering and Stable Warm White‐Light‐Emitting Diodes. Issue 37 (31st July 2017) - Wang, Zifei; Yuan, Fanglong; Li, Xiaohong; Li, Yunchao; Zhong, Haizheng; Fan, Louzhen; Yang, Shihe
Abstract : Red emissive carbon quantum dots (R‐CQDs) with quantum yield of 53% is successfully prepared. An ultraviolet (UV)‐pumped CQD phosphors‐based warm white light‐emitting diode (WLED) is realized for the first time and achieves a color rendering index of 97. This work provides a new avenue for the exploration of low cost, environment‐friendly, and high‐performance CQD phosphors‐based warm WLEDs. Abstract : Red‐emissive carbon quantum dots (R‐CQDs) with a quantum yield of 53% are successfully prepared. An ultraviolet (UV)‐pumped CQD‐phosphorbased warm‐white‐light‐emitting diode (WLED) is realized for the first time, which achieves a color rendering index of 97. A new avenue for the exploration of low cost, environmentally friendly, and high‐performance CQD‐phosphorbased warm WLEDs is thus provided.